(untitled) (The Journal of Forensic Accounting Profession, 2023)
Forensic accountants need to respond to the ever-growing global threat of financial crime and the continuing need for expertise within the area of financial dispute work. The global development of forensic accounting as a discipline has been ad hoc, and this paper will focus on the two most developed nations regarding the expansion of forensic accounting i.e., the USA and the UK. From this study two major themes have emerged: that of the status of the regulation and education of forensic accountants within the USA and the UK and we ultimately call for radical reform in both areas. Currently there is no recognised regulatory body which encompasses all aspects of a forensic accountant’s role, thus there is no standard code of ethics which practicing forensic accountants are obliged to follow. In addition, the absence of a recognised educational route to becoming a forensic accountant has resulted in a lack of awareness of the role as a potential career path and makes succession planning within forensic accounting firms problematic. (Previously published on Sciendo: https://sciendo.com/article/10.2478/jfap-2023-0002, pod licencom CC BY-NC-ND 4.0)